Monitoring of the changes in chemical composition of gases in a plasma chemical reactor during condensation of the reaction products using the acoustic-wave frequency data; Russian Physics Journal; Vol. 44, iss. 5 - Remnev G. E. Gennady Efimovich; Pushkarev A. I. Aleksandr Ivanovich; Pushkarev M. A.; Krasil'nikov V. A.; Guzeeva T. I. (2001, 2001)
Title screen